Factors Influencing Stock Valuation: A Systematic Review of the Role of Market Fundamentals and Sentiment - Hafidz, Nida Shaffitry (PT. Global World Scientific, 2025)
Stock valuation is a crucial aspect of investment decision-making, influenced by both company fundamentals and market sentiment. This study aims to systematically examine the influence of these two factors through a Systematic Literature Review (SLR) approach on literature published between 2020 and 2024 in the ScienceDirect database. The analysis of 10 articles shows that fundamental indicators such as financial performance, financial ratios, and revenue growth significantly influence stock valuation. However, market sentiment, including investor opinion, news coverage, and social media activity, also plays a significant role in shaping stock prices, often leading to deviations from fundamental values. This study emphasizes the importance of an approach that considers the interaction between fundamental factors and market sentiment for a more comprehensive understanding of stock valuation dynamics.